Farmer’s knowledge and suggested approaches for controlling aflatoxin contamination of raw milk in Pakistan - Yunus, Agha Waqar; Lindahl, Johanna Frida; Anwar, Zahid; Ullah, Aman; Ibrahim, Mohammed Nawaz Mohammed (Frontiers in Microbiology, 2022)
Monitoring of aflatoxin levels in milk is often complicated in developing countries due to the dominance of informal markets channeling milk in raw form. Farmer’s awareness and participation in aflatoxin mitigation can be critical in such scenarios. Therefore, the present study was conducted to understand the perceptions of dairy farmers about aflatoxins and link it with aflatoxin mitigation programs on milk in Pakistan. Information was collected from 450 peri-urban dairy farmers in seven cities using questionnaires. Majority (77.9%) of the farmers were aware of the negative impact of moldy feed on animal health. However, only 40.6% of the farmers were aware of the transferability of the toxins from moldy feed to milk. The farmers had almost no awareness of aflatoxins as 95% never heard of the term. After receiving an onsite briefing on effects of the toxin on animal and human health, and its transferability to milk, 98.3% farmers showed willingness to buy aflatoxin-safe feedstuffs, while 88.5% showed willingness to control aflatoxin in milk. Around half of the farmers considered aflatoxin control programs as affordable. On average, farmers agreed to pay 10.1% higher price for aflatoxin certified oilseed cakes. Availability of feedstuffs certified of low aflatoxin content was suggested by 22% of the participants as the critical step in reducing aflatoxins in milk. Other important suggestions included; subsidy on quality feeds (18%), raising awareness (18%), and legislation and monitoring (16%). The present results suggest that the current practice of milk monitoring in the country can yield desirable results only if it is coupled with feed certification programs ensuing availability of aflatoxin-safe feeds. Further, awareness can positively impact participation of producers in aflatoxin control programs. In this regard, awareness about effects of aflatoxins on animal health was found to be a more powerful trigger of willful control compared with the awareness of the toxin’s transferability to milk.